Comparative analysis of the experimental dilation of some materials used in the manufacture of physiognomic fixed prosthetic restorations - Mirel Stoian-Albulescu; Doina Lucia Ghergic; Costin Coman; Raluca-Monica Comaneanu; Oana Botoaca; Dan Nicolae Patroi (Amaltea Medical Publishing House, 2022)
Aim of the study was the comparative analysis of the experimental dilation of some materials used in the fabrication of physiognomic fixed prosthetic restorations. Material and methods. 3 biomaterials used in the fabrication of physiognomic fixed prosthetic restorations, pressed ceramic IPS e.max Press Ivoclar Vivadent, WhitePeaks Copra Smile (ZrO2, 600 MPa) and WhitePeaks Copra Supreme (ZrO2, 1100 MPa) were comparatively analyzed. The temperature increase was carried out from 20OC to 400OC, with the speed of 2 degrees/minute in a dilatometer. The repetition of the heating was done 2 times, with a 30-minute break between attempts. Results. The smallest expansion occurred for the e.max sample, followed by Zr600 and Zr1100. Conclusions. The present study demonstrated the production of a thermal expansion at the level of pressed ceramics and biomaterials based on zirconium dioxide upon experimental heating in the range of 20-400OC in dilatometer. Subjecting pressed ceramic or zirconium dioxide prosthetic restorations to high temperatures during the clinical-technical phases of occlusal processing/adaptation without adequate cooling may introduce residual thermal stresses into the material structure, which may subsequently lead to cracking of the prosthetic restorations under stress conditions determined by masticatory forces.